The importance of sandeel (Ammodytes marinus) for minke whales (Balaenoptera acutorostrata) and white-beaked dolphins (Lagenorhynchus albirostris) in Faxaflói Bay, Iceland - Freydís Ósk Hjörvarsdóttir 1991- (2014)
Faxaflói Bay, located at the southwest coast of Iceland, has been noted as important feeding grounds for both minke whales (Balaenoptera acutorostrata) and white-beaked dolphins (Lagenorhynchus albirostris). These two cetacean species are both known to prey on lesser sandeels (Ammodytes marinus), a high-energy prey, which are found in high density in Faxaflói Bay. The aim of the study was to investigate the predator-prey relationship between sandeels and both minke whales and white-beaked dolphins, and whether changes in population parameters of the sandeel stock influence the abundance of these cetacean species in Faxaflói Bay. Whale abundance was estimated from observational data collected in regular whale watching tours in July 2008-2013. Sandeel data from the same period comes from a monitoring programme where fish was caught by a dredge or a trawl. Age structure of the sandeel stock was determined by ageing individuals with otolith analysis. Minke whale abundance showed a significant correlation to the proportion of older sandeels (one year old and older). When the proportion of older sandeel in the stock was high more minke whales were seen. A similar analysis found no relationship between the abundance of white-beaked dolphins and the proportion of older sandeels. The results from this study suggest that the abundance of older sandeels is of greater importance for minke whales than for white-beaked dolphins. How these two predator species respond to fluctuations in prey populations might be linked to differences in their foraging behaviour and their dependency of prey density. Faxaflói er staðsettur á suðvestur strönd Ísland og hefur verið talinn vera mikilvægt fæðu svæði fyrir bæði hrefnu (Balaenoptera acutorostrata) og hnýðing (Lagenorhynchus albirostris). Þessar tvær tegundir nýta sandsíli, há-orku fæðutegund, sem finnst í miklum þéttleika í Faxaflóa. Markmið rannsóknarinnar var að rannsaka afræningja-bráðar sambandið á milli sandsíla og bæði hrefnu og hnýðinga, og hvort breytingar í sandsíla ...